Inferring User Needs & Tasks from App Usage Interactions - Tian, Yuan (2022)
Mobile devices have become an increasingly ubiquitous part of our everyday life, which are not only used for basic communication. Nowadays, the need for mobile services arises from a broad range of requirements including both single app usage (e.g., check on the weather) and complex task completion (such as planning vacation) which may lead to lengthy operations within distinct apps. Understanding how users interact with apps could provide us with great signals for profiling users and help service providers/app developers/smartphone manufacturers to improve user experience and retention. Therefore, in this thesis, we present work towards inferring user needs and tasks from their app usage interactions.